2004
DOI: 10.1159/000075628
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Renal Function Studies in Severe Hypothyroidism and after Thyroid Hormone Replacement Therapy

Abstract: Aim: To investigate the possible changes in the renal tubular function in severe short-term hypothyroidism using 99mTc-MAG3 renography. Methods: 27 consecutive thyroidectomized patients (7 males and 20 females) aged 19–79 (mean 53) years were included in the present study. 99mTc-MAG3 renography was performed in all patients before and after thyroid hormone replacement therapy. In addition, 51Cr-EDTA clearance and serum creatinine concentrations were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 18 publications
5
60
0
3
Order By: Relevance
“…Nikkila showed that a moderate increase in serum triglycerides in hypothyroid patients [13]. Jaiprabhu [5] also reported about hyperlipidemia in hypothyroid patients [10]. All of these studies support our results.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Nikkila showed that a moderate increase in serum triglycerides in hypothyroid patients [13]. Jaiprabhu [5] also reported about hyperlipidemia in hypothyroid patients [10]. All of these studies support our results.…”
Section: Resultssupporting
confidence: 89%
“…In general population a high prevalence of gout and hyperuricemia is found mainly due to impaired renal plasma flow and altered glomerular filtration rate [9]. However hyperuricemia is secondary in case of hypothyroid patients [10]. Some study revealed that in women, hypothyroid status was not associated with hyperuricemia or gout whereas hypothyroid is not associated with hyperuricemia in male also [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hypo-or hyperthyroidism may affect renal tubular function, glomerular filtration rate (GFR) and proteinuria (7). Hypothyroidism has been associated with increased serum creatinine (Scr) and decreased GFR (8)(9)(10). On the other hand, thyrotoxicosis has been associated with increased GFR and renal blood flow (RBF) with a concomitant reduction of Scr (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The clearance of OPG or its metabolism was reported to be under the influence of renal function (31) and creatinine clearance could be influenced by thyroid hormone (32). Although we have no data about the creatinine clearance, serum creatinine did not change significantly before and after L-T4 replacement therapy ( Table 3).…”
Section: Discussionmentioning
confidence: 81%